Mekanisme Penyelesaian Sengketa Pelanggaran Hak Cipta atas Pemutaran Musik secara Komersial : Studi Sengketa antara Lembaga Manajemen Kolektif dengan Outlet Mie Gacoan di Denpasar - I Gusti Agung Wahyu Artha Kusuma Putra; I Nyoman Budiana; Putu Eva Ditayani Antari; I Gusti Ayu Eviani Yuliantari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the inconsistency between legal norms and practice in the use of music for commercial purposes without proper licensing and royalty payments. Despite clear regulations under Indonesian Copyright Law, violations remain frequent, as reflected in the dispute between the Collective Management Organization and a Mie Gacoan outlet in Denpasar. This research aims to examine the legal framework governing commercial music use and to analyze the dispute resolution mechanism applied in the case. The study employs a normative legal research method using statutory and conceptual approaches, supported by secondary legal materials such as legislation, legal doctrines, and relevant literature. The findings indicate that the commercial use of music without authorization constitutes a violation of the economic rights of creators. The dispute was resolved through mediation as a form of alternative dispute resolution, resulting in an agreement on royalty payment as compensation. This outcome highlights the effectiveness of non-litigation mechanisms while also revealing a gap between regulatory provisions and their implementation in practice. Strengthening legal awareness and enforcement is therefore essential to ensure optimal copyright protection.